A note on apparent solar time and the seasonal cycle of atmospheric solar tides. (13th July 2017) - Hamilton, Kevin; Sakazaki, Takatoshi
Abstract : Both observations and comprehensive model simulation data of atmospheric fields are generally available at fixed Mean Solar Times through the day, which is convenient as the notional 'mean sun' progresses around the Earth each day in exactly 24 h. This article reports on a simple investigation of the effect of correcting data taken in Mean Solar Time to account for the difference in position between the actual (or 'apparent') sun and the mean sun, with a focus on characterizing atmospheric tidal oscillations. In particular, we found that the annual cycle in the phase of the semidiurnal atmospheric tidal oscillation of surface pressure near the Equator is almost entirely explained by the difference between Mean Solar Time and Apparent Solar Time. This result was confirmed in raw barometric observations as well as in several global reanalysis datasets. Abstract : Observations and model simulations of atmospheric tides are significantly affected by the difference in position between the actual (or 'apparent') sun and the notional 'mean' sun used to define mean solar time and universal time. The annual cycle in the phase of the semidiurnal atmospheric tidal oscillation of surface pressure near the Equator is almost entirely explained by this effect.